2016
DOI: 10.1155/2016/2014201
|View full text |Cite
|
Sign up to set email alerts
|

The Hypertension of Hemophilia Is Not Explained by the Usual Cardiovascular Risk Factors: Results of a Cohort Study

Abstract: Background. The etiology of the high prevalence of hypertension among patients with hemophilia (PWH) remains unknown. Methods. We compared 469 PWH in the United States with males from the National Health and Nutrition Examination Survey (NHANES) to determine whether differences in cardiovascular risk factors can account for the hypertension in hemophilia. Results. Median systolic and diastolic BP were higher in PWH than NHANES (P < 0.001) for subjects not taking antihypertensives. Those taking antihypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 37 publications
0
38
1
Order By: Relevance
“…One of our previous studies, comparing a cohort of nearly 600 PWH with gender‐, age‐, and race‐matched subjects from the general population, showed that higher blood pressure measurements were not explained by differences in the usual risk factors. While risk factors such as BMI, smoking, dyslipidemia, diabetes, and renal function were associated with systolic and diastolic blood pressures, their prevalence was similar or lower in PWH compared to the general population. Likewise, infection with hepatitis C or HIV, which are relatively common in older PWH, did not explain higher blood pressures in PWH.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…One of our previous studies, comparing a cohort of nearly 600 PWH with gender‐, age‐, and race‐matched subjects from the general population, showed that higher blood pressure measurements were not explained by differences in the usual risk factors. While risk factors such as BMI, smoking, dyslipidemia, diabetes, and renal function were associated with systolic and diastolic blood pressures, their prevalence was similar or lower in PWH compared to the general population. Likewise, infection with hepatitis C or HIV, which are relatively common in older PWH, did not explain higher blood pressures in PWH.…”
Section: Introductionmentioning
confidence: 71%
“…While risk factors such as BMI, smoking, dyslipidemia, diabetes, and renal function 4,5,7 were associated with systolic and diastolic blood pressures, their prevalence was similar or lower in PWH compared to the general population 5 . Likewise, infection with hepatitis C or HIV, which are relatively common in older PWH, did not explain higher blood pressures in PWH 5 . Furthermore, even after treatment with antihypertensive drugs, PWH still had higher blood pressure values than ordinary males treated with such drugs.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Numerous articles have reported a higher prevalence of hypertension in PWH than that in the general population. 24,25 In this study, the prevalence of hypertension defined as a blood pressure of ≥140/90 mm Hg was similar in Japanese PWH as compared to that in the general male population (age-adjusted OR 1.164, P = 0.107; Table 3), whereas the prevalence of hypertension defined more strictly as a blood pressure of ≥130/85 mm Hg was significantly lower in the PWH than that in the general male population (age-adjusted OR 0.797, P = 0.014; Table 3). Caution is needed in regard to the following points while interpreting our findings.…”
Section: Ta B L E 3 Comparison Of the Risk Factors Between Adult Malementioning
confidence: 99%